ANALISIS BEBERAPA SIFAT KIMIA TANAH PADA DUA MACAM PENGGUNAAN LAHAN DI SUNGAI KAKAP, KABUPATEN KUBU RAYA, KALIMANTAN BARAT - Fadilla, Ulfia; Nusantara, Rossie Wiedya; Manurung, Rinto (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2024)
Paddy fields and mixed farming apply intensive agricultural cultivation, and sustainable land use causes changes in land quality, one of which affects soil chemical properties. This study aimed to compare soil chemical properties based on differences in the use of paddy fields and mixed farming in Sungai Kakap District, Kubu Raya Regency, West Kalimantan. Research in the field in Pal IX Village, Sungai Kakap Sub-district, Kubu Raya Regency, for sampling soil samples at 0-20 cm depth. Soil analysis was conducted at the Chemistry and Soil Fertility Laboratory, Faculty of Agriculture, Tanjungpura University. The results showed that the two fields, paddy fields, and mixed farming, had almost the same chemical properties in paddy fields pH, organic C, available P, cation exchange capacity (CEC), exchangeable Ca and exchangeable Mg.